2018
DOI: 10.1002/ddr.21471
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive, anti‐inflammatory, and central nervous system (CNS) effects of the natural coumarin soulattrolide

Abstract: Soulattrolide is a natural coumarin synthesized by the leaves of species of Calophyllum (Calophyllaceae) rain forest trees, including the American C. brasiliense, and the Asian C. teysmanii. Soulattrolide is a potent inhibitor of the reverse transcriptase from HIV‐1 (RT‐HIV‐1), and active against Mycobacterium tuberculosis. However, the effects of this coumarins on other systems, remains to be evaluated. C. brasiliense is used in traditional medicine for the treatment of pain and inflammation. Therefore, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…We have demonstrated that the mice that received the topical application of (DMC) 2 @β-CD (FL) demonstrated a qualitative reduction of granulation tissue in relation to the saline group (Figure 6), probably due to the anti-inflammatory action of the coumarins as already demonstrated in other studies. 27 In wound repairs, it has been shown that less inflammatory activity leads to better healing, more similar to the regeneration process. [9][10][11]68 One of the cells that helps decrease the area of granulation tissue 7 days after the injury is mast cells, which are decreased in the groups that received a topical application of coumarins.…”
Section: In Vivo Wound Healing Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…We have demonstrated that the mice that received the topical application of (DMC) 2 @β-CD (FL) demonstrated a qualitative reduction of granulation tissue in relation to the saline group (Figure 6), probably due to the anti-inflammatory action of the coumarins as already demonstrated in other studies. 27 In wound repairs, it has been shown that less inflammatory activity leads to better healing, more similar to the regeneration process. [9][10][11]68 One of the cells that helps decrease the area of granulation tissue 7 days after the injury is mast cells, which are decreased in the groups that received a topical application of coumarins.…”
Section: In Vivo Wound Healing Studiesmentioning
confidence: 99%
“…The anti-inflammatory activity of coumarins in repairing skin wounds has not yet been demonstrated. However, it has been shown to reduce edema in rabbit ears and mouse paws. , Therefore, the insolubility of some compounds in water restricts the application of drugs in some biological studies. In addition, poorly soluble drugs have bioavailability problems, with dissolution being the limiting factor for their absorption in the body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropathic pain (NP) is caused by primary nervous system injury and dysfunction, which seriously affects the quality of patients' life (Barragan-Iglesias et al, 2014;Alonso-Castro et al, 2018). At present, treatment options for NP include nerve block with anesthetics, opioid receptor antagonism, nerve damage, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathic pain inducing by a primary lesion or disease affecting the somatosensory system is a devastating disease which mainly manifested as hyperalgesia, allodynia and spontaneous pain, and comorbidities such as anxiety, depression and sleep disorder, which seriously affects patients' quality of life and bring extreme financial burden to the country [1][2][3]. The theory and practice of pain treatment have long focused on neurons and designed therapeutic plan on these grounds.…”
Section: Introductionmentioning
confidence: 99%